1997
DOI: 10.1177/10454411970080030501
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts On Adhesion To Dentin

Abstract: This review examines fundamental concepts in bonding to dentin. Emphasis is placed on the structure and permeability characteristics of dentin and how they may influence its interaction with adhesive resin. Several new techniques to examine the interfaces between resin and dentin are reviewed along with some of their limitations. The advantages and disadvantages of acid etchants/conditioners vs. self-etching conditioners/primers are discussed. The problems of matching the surface tension of resin-bonding syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
207
1
27

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(239 citation statements)
references
References 104 publications
4
207
1
27
Order By: Relevance
“…Several studies have demonstrated better sealing ability in enamel than in dentin margins. 6,[32][33] However, according to Eick and others, 34 with the evolution of adhesive systems, similar bonding values could be achieved in enamel and dentin, primarily after hybridization of the dentin tissues. In Class II composite restorations, no significant difference was found for margins located in enamel or dentin, regarding the sealing ability or microtensile bond strength of the interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated better sealing ability in enamel than in dentin margins. 6,[32][33] However, according to Eick and others, 34 with the evolution of adhesive systems, similar bonding values could be achieved in enamel and dentin, primarily after hybridization of the dentin tissues. In Class II composite restorations, no significant difference was found for margins located in enamel or dentin, regarding the sealing ability or microtensile bond strength of the interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…The homogenous and thorough resin infiltration and entanglement of exposed collagen fibrils in wet demineralized dentin are the primary factors critical in determining an adequate adhesive/dentin (a/d) hybrid layer [1][2][3]. BisGMA (Bisphenol-A-glycerolate (1-glycerol/ phenol) dimethacrylate), a widely used component in dentin adhesives has very good mechanical properties after curing, but this component is relatively hydrophobic and thus, does not adequately infiltrate the wet demineralized dentin collagen [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…These inadequacies can include incomplete alteration and/or removal of smear layer components due to composition (pH, osmolality) and strength of the acidic primer, and inadequate resin film thickness, requiring multiple layering techniques and changes in the monomer/water ratio, resulting in phase separations. [1][2][3]9,16,[19][20][21][22] Morphological and histological considerations, and other clinical factors causing inadequate bonding at the material/tooth surface interface, include cavity configuration (C-factor) and dentinal tubule/enamel rod orientation, capillary movement of dentinal tubular fluids, physical characteristics of the restorative material (filler loading, volumetric expansion, modulus of elasticity and polymerization contraction), inadequate margin adaptation of the restorative material during insertion, inappropriate barrier protection (dental rubber dam), tooth location, occlusal stresses/tooth flexure and patient age considerations. [23][24][25][26][27][28][29][30][31] In this study, since hybrid layer morphology was not evaluated microscopically, the specific nature of restoration failure (microleakage) for each adhesive system is unknown, although several factors were strongly suspected: inefficiency of acidic monomers in alteration of the smear layer for classic hybrid layer formation, cavity C-factor, orientation of dentinal tubules/enamel rods to the cementoenamel junction, use of acetone-based solvent primer systems and post-treatment stresses caused by polymerization contraction.…”
mentioning
confidence: 99%